Regards sur le séisme de Mexico de septembre 2017 : permanences et décalages par rapport à la catastrophe de 1985 - Jean-François Valette (EchoGéo)
On September 19th of, 2017, thirty-two years after the 1985 earthquake that killed more than 10,000 persons, a new deadly earthquake shook Mexico-City. If the damage is relatively small in comparison with 1985 and in relation to the size of the city itself, the parallel is inevitable. It nevertheless requires to be analyzed focusing on the differences between the two catastrophes, geological and of course, political and social. By confronting a press review on the recent earthquake and analyzing the current urban context of the metropolis, this article aims to understand how Mexico-City resisted relatively well, but also how the recent crisis has cruelly highlighted on the one hand the socio-spatial inequalities within the agglomeration, and on the other hand, the weaknesses of the Mexican State. It will be a question of comparing the two traumatic events of 1985 and 2017. Then, the factors of the "best resistance" of 2017 will be observed, in particular in terms of risk management policies. Finally, we will show how the urban dynamics of the last decades raise issues of vulnerabilities and exacerbated inequalities, highlighted by the recent earthquake.